Solid waste management by considering composting potential in Malaysia toward a green country - Sanaz Saheri,; Masoud Aghajani Mir,; Noor Ezlin Ahmad Basri,; Rawsan Ara Begum,; Noor Zalina Mahmood, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
Solid waste disposal has become a serious issue for country and municipal governments throughout the nation. As available landfill space decreases and the cost of siting and building new landfill increases, local authorities are struggling to develop alternative means of meeting the waste disposal challenge. Landfilling is the most widely used method for solid waste disposal in countries with tropical settlement. Landfills have created various environmental problems such as emissions and leachate. The public has become more aware concerning landfill issues such as increasing concern on the groundwater contamination, potential release of toxic gases and odor. A big part of these problems come from organic waste into the solid waste. Municipal solid waste in Malaysia has a large percent of food waste (around 50-60 percent) that makes a lot of problems in disposal methods. It has emerged as a potentially viable means by which local governments can reduce the volume of waste entering landfills by diverting the organic fraction. Composting is a biological process, in which the organic matter is biodegraded by microorganisms under controlled conditions of temperature, moisture content, oxygen, PH and the retention time that can be initiated by mixing biodegradable organic matter with bulking agents to enhance the porosity of the mixture. In this study, a composting plant in Malaysia is considered that uses organic waste from the market (market waste). Five tons organic waste per day is received in the plant, and it is treated by the wind raw composting method. After calculating costs and benefits of this method result shows that total quantitative benefit of this plant is not much higher than a total quantitative cost but this result is just for quantitative parameter. This method has a lot of qualitative benefits such as: reducing the amount of municipal solid waste, transportation cost of carrying municipal solid waste to land fill, emissions and leachate of landfill, increasing life span of landfill and reducing land use. Composting organic materials that have been diverted from landfills ultimately avoids the production of methane and leachate formulation in the landfills regarding to 50 percent of organic waste in municipal solid waste of Malaysia. With removing this amount of waste from MSW with using composting method, not only the environmental problems of land filling can be reduced but also the costs of transportation and other costs of disposal can be reduced by 50%. Because of one of the most important problems in tropical settlement is to find proper methods to dispose of municipal solid waste toward decreasing pollution, producing compost can be a suitable way but expanding of this treatment method in Malaysia closely related to economic governmental supports